2021
DOI: 10.1371/journal.pone.0259687
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Salmonella spp. and Listeria monocytogenes strains from biofilms in cattle and poultry slaughterhouses located in the federal District and State of Goiás, Brazil

Abstract: Listeria monocytogenes and Salmonella spp. are considered important foodborne pathogens that are commonly associated with foods of animal origin. The aim of this study was to perform molecular characterization of L. monocytogenes and Salmonella spp. isolated from biofilms of cattle and poultry slaughterhouses located in the Federal District and State of Goiás, Brazil. Fourteen L. monocytogenes isolates and one Salmonella sp. were detected in poultry slaughterhouses. No isolates were detected in cattle slaughte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 103 publications
1
8
0
1
Order By: Relevance
“…Our study addressed the gap in data related to genomic characterization of U.S. ruminant listeriosis isolates. We identified a significant number of lineage 3 isolates associated with ruminant listeriosis, which had not been observed in larger isolate sets from cases in other geographic locations ( 12 , 40 , 42 ). With these data, we illustrated the associations between lineage and clinical manifestations in the region, as well as overlaps between frequently isolated sublineages from ruminants and those from human cases.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Our study addressed the gap in data related to genomic characterization of U.S. ruminant listeriosis isolates. We identified a significant number of lineage 3 isolates associated with ruminant listeriosis, which had not been observed in larger isolate sets from cases in other geographic locations ( 12 , 40 , 42 ). With these data, we illustrated the associations between lineage and clinical manifestations in the region, as well as overlaps between frequently isolated sublineages from ruminants and those from human cases.…”
Section: Discussionmentioning
confidence: 68%
“…Although L. monocytogenes rarely develops resistance to antibiotics, some studies have reported an increased presence of AMR genes in isolates from different sources. In Brazil, for example, AMR was detected in around 57% of the isolates recovered from cattle and poultry slaughterhouses, with resistance to sulfonamides the most common feature, along with the presence of tetC , ermB , and tetB ( 40 ). Similarly, a study conducted in France that included isolates from food and environmental sources over a 10-year period found isolates resistant to erythromycin, tetracycline, and trimethoprim and detected ermB , tetM , and dfrD among other genes associated with antimicrobial resistance ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…The in vitro biofilm-forming capability was evaluated as described by Agostinho Davanzo et al . [ 57 ] and Borges et al . [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…The intestinal barrier represents the initial defense against L. monocytogenes infection, and InlA is pivotal for enabling the bacteria to invade [ 14 ]. A lot of studies have reported that PMSCs in InlA, resulting in a truncated form of InlA, suggesting attenuated pathogenicity [ 15 , 16 ]. For example, in the United States, the detection of L. monocytogenes strains harboring stop codons has been demonstrated at 35–45% in food isolates, while human isolates only account for 5.1% [ 17 ].…”
Section: Introductionmentioning
confidence: 99%